2017
DOI: 10.1186/s12884-017-1330-8
|View full text |Cite
|
Sign up to set email alerts
|

Study protocol: evaluation of the probiotic Lactobacillus Fermentum CECT5716 for the prevention of mastitis in breastfeeding women: a randomised controlled trial

Abstract: BackgroundMastitis and accompanying pain have been associated with the cessation of breastfeeding. Mastitis is an inflammatory condition of the breast and may be a result of decreased immunity and a lowered resistance to infection. Mastitis affects up to one in five breastfeeding women with most episodes occurring in the first 6–8 weeks postpartum. Antibiotics are often used in the treatment of mastitis, but have not been popular or proven effective as a preventative agent. The WHO has highlighted significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 36 publications
(53 reference statements)
0
27
0
4
Order By: Relevance
“…With regards to maternal health, studies have demonstrated that ingestion of human milk derived probiotic strains L. fermentum CECT5716 and L. salivarius CECT5713 resulted in significant reduction in Staphylococcus load, reduced breast pain, faster recovery, and lower reoccurrence rates of mastitis over lactation, thus suggesting an effective alternative to antibiotics for the treatment of mastitis during lactation [231,257,258]. Further investigations documented the use of L. fermentum CECT5716 as a preventative measure for mastitis [259], with positives results also being reported for the use of L. salivarius PS2 as a preventative measure for mastitis [260].…”
Section: Maternal Implications Of Breast Feedingmentioning
confidence: 99%
“…With regards to maternal health, studies have demonstrated that ingestion of human milk derived probiotic strains L. fermentum CECT5716 and L. salivarius CECT5713 resulted in significant reduction in Staphylococcus load, reduced breast pain, faster recovery, and lower reoccurrence rates of mastitis over lactation, thus suggesting an effective alternative to antibiotics for the treatment of mastitis during lactation [231,257,258]. Further investigations documented the use of L. fermentum CECT5716 as a preventative measure for mastitis [259], with positives results also being reported for the use of L. salivarius PS2 as a preventative measure for mastitis [260].…”
Section: Maternal Implications Of Breast Feedingmentioning
confidence: 99%
“…Antibiotics are often used in the treatment of mastitis, but have not been popular or proven effective as a preventative agent. Increasing research indicates that specific probiotic bacteria possess significant anti-inflammatory properties and supports their potential use as immunomodulatory agents [45]. Supplementation with lactobacilli and probiotics may eliminate the risk of mastitis in women and prevent breast infection.…”
Section: Discussionmentioning
confidence: 99%
“…опубликовали данные рандомизированного двойного слепого плацебо-контролируемого исследования по оценке эффективности приема Lactobacillus fermentum CECT5716 в течение 8 недель после родов кормящей женщиной [21]. Исследователи заключили, что использование данного пробиотического штамма лактобактерий увеличивает продолжительность грудного вскармливания, снижает необходимость в использовании антибактериальных препаратов, тем самым является безопасным и эффективным средством профилактики лактационного мастита [21]. Пациентки с наличием местной клинической симптоматики мастита отмечали значительное уменьшение болевых ощущений с первой недели приема препарата, содержащего Lactobacillus fermentum CECT5716 [17].…”
Section: Medicinskij Sovetunclassified